Perspectives on commercializing innovation / edited by F. Scott Kieff, Troy A. Paredes. - Kieff, F. Scott; Paredes, Troy (Cambridge University Press, 2012)
Intellectual property is a vital part of the global economy, accounting for about half of the GDP in countries like the United States. Innovation, competition, economic growth and jobs can all be helped or hurt by different approaches to this key asset class, where seemingly slight changes in the rules of the game can have remarkable impact. This book brings together diverse perspectives from the fields of law, economics, business and political science to explore the ways varying approaches to intellectual property can positively and negatively impact our economy and society. Employing approaches that are both theoretically rigorous and grounded in the real world, Perspectives on Commercializing Innovation is well suited for practising lawyers, managers, lawmakers and analysts, as well as academics conducting research or teaching in a range of courses in law schools, business schools and economics departments, at either the undergraduate or graduate level.